TRENDS OF INNOVATIVE SOCIO-ECONOMIC DEVELOPMENT OF THE RUSSIAN INDUSTRY - Violetta V. Rokotyanskaya; Alexey N. Gerasimov; Galina V. Sarkisyants (Статистика и экономика, 2016)
Article is devoted to the task of accelerated social and economic development in the context of rather low performance of industrial production. In this context tendencies ofindexes of costs of production and sale of production, laborproductivity, capital productivity and indexes of production by the processing and hi-tech types of economic activityare analyzed. It is shown that for giving to the industry ofcharacter of the driver providing the reproduction growth ofall national economy it is necessary to concentrate priorityefforts on development of innovative productions. As it is represented, innovative productions are capable to makecardinal changes to the developed contradictory pattern of proﬁtability and productivity business of processes. However, successful implementation of this direction requires additional resources as the scale of the modern innovative productions in itself remains insigniﬁ cant. Therefore extension of an innovative component of national reproductionis the main administrative objective of an industrial policy.